Development and Characterization of Stingless Bee Propolis Properties for the Development of Solid Lipid Nanoparticles for Loading Lipophilic Substances - Putthiporn Khongkaew; Watcharaphong Chaemsawang (International Journal of Biomaterials)
Stingless bees are insects which are popularly bred by agriculturists in the eastern region of Thailand for the pollination of their orchards. The products from stingless bee breeding include bee honey and bee propolis. The objective of this experiment is to study the possibility of developing stingless bee propolis wax into solid lipid nanoparticles (SLN) by the comparison of five surfactants (Brij 721, Cremophor WO 7, Myrj 52, Poloxamer 188, and Tween 80). Each surfactant is used at three concentrations: 10%, 20%, and 30%. A master formula is selected according to the following: physical features, particle size, zeta potential, and entrapment. The results showed that Brij 721 and Myri 52 at 20% can be used in preparing SLN and have good preservation properties for vitamin E (size: 451.2 nm and 416.8 nm, zeta potential: - 24.0 and - 32.7; % EE: 92.32% and 92.00%, resp.). Therefore, they are further developed by adding the following drugs at low solubility: curcumin, ibuprofen, and astaxanthin. It is found that a formula using the surfactants Brij 721 and Myrj 52 at 20% have similar drug entrapment. The entrapment study involves curcumin 82%, ibuprofen 40%, and astaxanthin 67%. Moreover, the cytotoxicity test of blank solid lipid nanoparticle found no toxicty in fibroblast cell line (CRL-2522). Therefore, from this study, it is determined that stingless bee propolis wax has the potential to be developed to provide more efficient SLN in the future.